MANAJEMEN SUMBER DAYA MANUSIA DALAM KONTEKS COACHING, MENTORING, DAN COUNSELING (CMC) - Razilu, Razilu (Jurnal Ilmiah Kajian Keimigrasian, 2024)
This study examines the integration of Coaching, Mentoring, and Counseling (CMC) as a comprehensive approach to human resource development in the immigration sector, specifically aimed at enhancing employee performance, motivation, and preparing future leaders. Using a literature review method, the research explores how CMC can holistically address both technical and emotional needs of employees, while also promoting leadership development. The findings indicate that CMC plays a significant role in improving employee well-being, increasing motivation, and developing adaptive leaders capable of navigating complex organizational challenges. However, the implementation of CMC in government institutions, including immigration offices, faces several challenges, such as overlapping roles between coach, mentor, and counselor, insufficient training, and limited managerial support. To address these issues, organizations must clearly define the roles and responsibilities within CMC, provide adequate training, and integrate the program into performance management systems. This study concludes that with the right organizational support and structured evaluation, CMC can effectively foster the next generation of leaders who are equipped to handle the dynamic and complex nature of the immigration sector.